Probiotic effects on immunity and microbiome in HIV-1 discordant patients - Blázquez-Bondia, Carlos; Parera, Mariona; Català-Moll, Francesc; Casadellà, Maria; Elizalde-Torrent, Aleix; Aguiló, Meritxell; Espadaler-Mazo, Jordi; Santos, José Ramon; Paredes, Roger; Noguera-Julian, Marc (Frontiers in Immunology, 2022)
Some HIV-1 infected patients are unable to completely recover normal CD4+ T-cell counts after achieving HIV-1 suppression with combined Antiretroviral Therapy (cART), hence being classified as immuno-discordant. The human microbiome plays a crucial role in maintaining immune homeostasis and is a potential target towards immune reconstitution. RECOVER (NCT03542786) was a double-blind placebo-controlled clinical trial designed to evaluate if the novel probiotic i3.1 (AB-Biotics, Sant Cugat del Vallès, Spain) was able to improve immune reconstitution in HIV-1 infected immuno-discordant patients with stable cART and CD4+ counts <500 cells/mm3. The mixture consisted of two strains of L.plantarum and one of P.acidilactici, given with or without a fiber-based prebiotic. Adverse event (AE) incidence was similar among groups (55%, 33%, and 53% in the Synbiotic, Probiotic and Placebo arms, respectively, the most common being grade 1 digestive AEs: flatulence, bloating and diarrhoea. Two grade 3 AEs were reported, all in the Synbiotic group, and 1 grade 4 AE in the Placebo. After 6 months, Synbiotic exposure was associated with a increased CD4+/CD8+ T-cell ratio vs baseline while wfter 9 months, CD4+ and CD4/CD8 ratio increased vs baseline sCD14 was lower than in the placebo. No effect in immune parameters was observed in the Probiotic arm. None of the two interventions modified microbial gene richness (alpha diversity). However, intervention as categorical variable was associated with slight but significant effect on beta diversity. Additionally, at month 6, Synbiotic intervention was associated with lower abundances of Assimilatory Sulphate Reduction, biosynthesis of methionine and cysteine than placebo. Probiotic detection in faeces was associated with significant decreases in C Reactive Protein (CRP) at month 6 vs baseline and lower IL-6 valuesvs non-detection. No detection was associated with higher CD4/CD8 ratio at month 6 vs baseline. After washout, probiotic non-detection, was also associated with a significant increase in CD4+ and CD4/CD8 ratio. A Synbiotic intervention with L.plantarum and P.acidilactici was safe and led to small increases in CD4/CD8 ratio and minor reductions in sCD14 of uncertain clinical significance. A probiotic with the same composition was also safe but did not achieve any impact on immune parameters or faecal microbiome composition.